Integrasi Problem Based Learning dengan STEM dalam Pembelajaran IPA terhadap Keterampilan Berpikir Kritis Siswa - dewannia fariska; Wardah Nabilah Hanum; Zefanya Nanda Prastiwi; Sri Wahyuni (Peneliti.net, 2023)
Critical thinking is a 21st century skill that needs to be improved in order to educate students to be accustomed to making decisions independently in dealing with a problem. The STEM-integrated PBL model has a syntax that can guide students in improving their critical thinking skills in science learning. Writing this article aims to analyze various literature regarding the integration of PBL and STEM in learning science as an innovation to develop students' critical thinking skills. Sources of information were obtained by analyzing 22 references from e-books, proceedings, international journals, accredited and non-accredited national journals. The research design used is narrative review. Based on the results of the analysis, it is known that STEM-integrated PBL-based learning can improve students' critical thinking skills to understand problems and solve them, especially during the science learning process.